ЎҚУВЧИЛАР ИНТЕЛЛЕКТУАЛ-МАЪНАВИЙ САВИЯСИНИНГ ЎСИШИДА КИТОБХОНЛИК МАДАНИЯТИНИНГ РЕАЛ ИМКОНИЯТЛАРИ ВА ИСТИҚБОЛЛАРИ - Холматова, С. (SCIENCE and SOCIETY, 2020)
In the article the author analysed the development of reading culture of learners and the hidden abilities of students and the importance of increasing the level of reading culture in the intellectual-spiritual development of the youth..